Variability in the southern margin of the Indo-Australian Summer Monsoon since 46 ka - Teresa Dixon; Rachel Rudd; Justine Kemp; Samuel Marx; Patrick Moss; Quan Hua; Michael Bird; Philip Anthony Hall; Hamish McGowan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Investigating the dynamics of freeze-drying and annealing using in-situ synchrotron X-ray microtomography - Shuai Bai Palmkron; Jonas Engqvist; Hans Bolinsson; Björn Bergenståhl; Stephen Hall; Samuel McDonald; Marie Wahlgren; Emanuel Larsson; Anna Millqvist Fureby (Food Hydrocolloids, 2025)

Hydroclimate variability in the eastern Kimberley, Australia, since the last deglaciation - Teresa Dixon; Rachel Rudd; Justine Kemp; Samuel Marx; Patrick Moss; John Nikolaus Callow; Philip Anthony Hall; Quan Hua; Hamish McGowan (Journal of Quaternary Science, 2025)
The climate of the Kimberley region in tropical northwest Australia is dominated by the Indo‐Australian summer monsoon (IASM). Understanding of the palaeoclimate since the Last Glacial Maximum in this region, which is well placed to record IASM variations, is currently based on few records. Many of these are confounded by local environmental factors such as topography, anthropogenic activity or marine processes. Here, we present a geochemical record spanning the last 17 ka, in conjunction with pollen and charcoal records from 5.4 ± 0.1 ka (1 sigma uncertainty) to the present. The record comes from the floodplain of the Bullo River and as such represents variations in the hydroclimate of its 2000 km 2 catchment. Results show that the deglacial was characterised by a variable monsoon until the onset of a wet interval beginning at 12.9 ± 0.9 ka. The exact onset and intensity of a dry period following 5 ka are uncertain, but conditions became progressively drier until the climate amelioration to modern conditions. These results are broadly consistent with previous research and extend our understanding of deglacial and Holocene hydroclimate variability to the eastern Kimberley, 350 km east of previously published Kimberley palaeoenvironmental records.

Imaging of Intracranial Aneurysms: A Review of Standard and Advanced Imaging Techniques - Sricharan S. Veeturi; Samuel Hall; Soichiro Fujimura; Mahmud Mossa-Basha; Elena Sagues; Edgar A. Samaniego; Vincent M. Tutino (Translational Stroke Research, 2025)

The Role of Temperature in the Termination of Dormancy in Zooplankton - Emma Svahn; Marcus Hall; Samuel Hylander (Marine Ecology, 2025)
Organisms in systems with seasonality require adaptations that enable them to endure harsh conditions and to emerge again at an optimal time to start a new period of production. One such adaptation is dormant eggs in zooplankton. While there is much information on the cues leading to the production of dormant eggs, less is known about the termination and hatching of these eggs, especially among marine zooplankton. Our results from a combined laboratory and field study at a coastal Baltic Sea site showed that hatching in some overwintering copepods was temperature‐dependent, with a threshold‐like initiation between 6°C and 9°C. In contrast, overwintering rotifers hatched in comparable abundances in all temperatures, once a similar amount of degree‐days had been accumulated. The field study demonstrated that nauplii started to appear when temperatures increased above 6.8°C and were more abundant close to the sediment than in surface water in early spring, matching the hatching threshold found in the laboratory. Various rotifers increased in abundance at different times during the spring phenology, but without any differences in abundance between deep and surface waters. Hence, the hatching of zooplankton dormant eggs in this system is temperature‐dependent, likely taxa‐specific, and continued climate change is predicted to have implications for the plankton phenology, mismatches, and food web composition.

Aspirin and Subarachnoid Haemorrhage in the UK Biobank - Frederick Ewbank; Jacqueline Birks; Benjamin Gaastra; Samuel Hall; Ian Galea; Diederik Bulters (Translational Stroke Research, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Spatial and temporal changes in buccal pressure during prey-capture in the trumpetfish (Aulostomus maculatus) - Samuel Tegge; Jason Hall; Steve Huskey (Zoomorphology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Natural acidification changes the timing and rate of succession, alters community structure, and increases homogeneity in marine biofouling communities - Norah E. M. Brown; Marco Milazzo; Samuel P. S. Rastrick; Jason M. Hall‐Spencer; Thomas W. Therriault; Christopher D. G. Harley (Global Change Biology, 2018)
Ocean acidification may have far‐reaching consequences for marine community and ecosystem dynamics, but its full impacts remain poorly understood due to the difficulty of manipulating p CO 2 at the ecosystem level to mimic realistic fluctuations that occur on a number of different timescales. It is especially unclear how quickly communities at various stages of development respond to intermediate‐scale p CO 2 change and, if high p CO 2 is relieved mid‐succession, whether past acidification effects persist, are reversed by alleviation of p CO 2 stress, or are worsened by departures from prior high p CO 2 conditions to which organisms had acclimatized. Here, we used reciprocal transplant experiments along a shallow water volcanic p CO 2 gradient to assess the importance of the timing and duration of high p CO 2 exposure (i.e., discrete events at different stages of successional development vs. continuous exposure) on patterns of colonization and succession in a benthic fouling community. We show that succession at the acidified site was initially delayed (less community change by 8 weeks) but then caught up over the next 4 weeks. These changes in succession led to homogenization of communities maintained in or transplanted to acidified conditions, and altered community structure in ways that reflected both short‐ and longer‐term acidification history. These community shifts are likely a result of interspecific variability in response to increased p CO 2 and changes in species interactions. High p CO 2 altered biofilm development, allowing serpulids to do best at the acidified site by the end of the experiment, although early (pretransplant) negative effects of p CO 2 on recruitment of these worms were still detectable. The ascidians Diplosoma sp. and Botryllus sp. settled later and were more tolerant to acidification. Overall, transient and persistent acidification‐driven changes in the biofouling community, via both past and more recent exposure, could have important implications for ecosystem function and food web dynamics.

Coenzyme Q10 protects renal proximal tubule cells against nicotine-induced apoptosis through induction of p66shc-dependent antioxidant responses - Istvan Arany; Anthony Carter; Samuel Hall; Tibor Fulop; Mehul Dixit (Apoptosis, 2017)

α-Tocopherol protects renal cells from nicotine- or oleic acid-provoked oxidative stress via inducing heme oxygenase-1 - Dustin K. Reed; Samuel Hall; Istvan Arany (Journal of Physiology and Biochemistry, 2015)

Evidence of land‐sea transfer of the zoonotic pathogen Campylobacter to a wildlife marine sentinel species - Johanna L. Baily; Guillaume Méric; Sion Bayliss; Geoffrey Foster; Simon E. Moss; Eleanor Watson; Ben Pascoe; Jane Mikhail; Romain Pizzi; Robert J. Goldstone; David G. E. Smith; Kim Willoughby; et al. (Molecular Ecology, 2015)
Environmental pollution often accompanies the expansion and urbanization of human populations where sewage and wastewaters commonly have an impact on the marine environments. Here, we explored the potential for faecal bacterial pathogens, of anthropic origin, to spread to marine wildlife in coastal areas. The common zoonotic bacterium Campylobacter was isolated from grey seals ( Halichoerus grypus ), an important sentinel species for environmental pollution, and compared to isolates from wild birds, agricultural sources and clinical samples to characterize possible transmission routes. Campylobacter jejuni was present in half of all grey seal pups sampled (24/50 dead and 46/90 live pups) in the breeding colony on the Isle of May (Scotland), where it was frequently associated with histological evidence of disease. Returning yearling animals (19/19) were negative for C . jejuni suggesting clearance of infection while away from the localized colony infection source. The genomes of 90 isolates from seals were sequenced and characterized using a whole‐genome multilocus sequence typing ( MLST ) approach and compared to 192 published genomes from multiple sources using population genetic approaches and a probabilistic genetic attribution model to infer the source of infection from MLST data. The strong genotype‐host association has enabled the application of source attribution models in epidemiological studies of human campylobacteriosis, and here assignment analyses consistently grouped seal isolates with those from human clinical samples. These findings are consistent with either a common infection source or direct transmission of human campylobacter to grey seals, raising concerns about the spread of human pathogens to wildlife marine sentinel species in coastal areas.

Biphasic effects of tonic stimulation of muscle nociceptors on skin sympathetic nerve activity in human subjects - Samuel C. Hall; Azharuddin Fazalbhoy; Ingvars Birznieks; Vaughan G. Macefield (Experimental Brain Research, 2012)

Autoimmunity and inflammation: murine models and translational studies - Samuel W. Hall; Anne Cooke (Mammalian Genome, 2011)

The effect of temperature on the coupling between phosphorus and growth in lacustrine bacterioplankton communities - Edward K. Hall; Andrew R. Dzialowski; Samuel M. Stoxen; James B. Cotner (Limnology and Oceanography, 2009)
Phosphorus (P) routinely limits microbial growth in freshwater ecosystems. The growth rate hypothesis (GRH) relates growth to biomass P content mechanistically through changes in ribosomal ribonucleic acid (rRNA). Although the GRH has been shown in cultured bacteria, less well understood is how GRH relationships are affected by interactions with environmental parameters such as temperature. To address this, we evaluated the relationship between bacterial biomass P, RNA: deoxyribonucleic acid (DNA) ratio, and growth rate in 47 northern temperate lakes. Although RNA:DNA ratio was positively correlated with bacterial biomass P : carbon (C), we found no correlation between growth rate and RNA:DNA or between growth rate and biomass P : C. There was, however, a significant effect of temperature on biomass P : C. We investigated the effect of temperature more directly using filter‐separated bacterial communities from two lakes during two seasons while experimentally manipulating temperature and resources. For the summer communities, bacterial production (BP) and biomass P were positively correlated, and the slope of that relationship increased with increasing temperature. In winter communities, BP and biomass P were again positively correlated; however, the slope of that relationship decreased with increasing temperature. The slope of the relationship between BP and biomass P is a metric of nutrient use efficiency and was strongly influenced by temperature. More importantly, bacterioplankton demonstrated seasonal acclimation or adaptation to in situ temperature, suggesting that studies evaluating multiple communities in time and space fail to find a clear relationship between temperature and bacterial metabolism because bacterial communities are locally adapted to in situ temperature.